Impact of Local Grid Refinements of Spherical Centroidal Voronoi Tessellations for Global Atmospheric Models (Communications in Computational Physics, 2018)
In order to study the local refinement issue of the horizontal resolution for aglobal model with Spherical Centroidal Voronoi Tessellations (SCVTs), the SCVTs areset to 10242 cells and 40962 cells respectively using the density function. The ratiobetween the grid resolutions in the high and low resolution regions (hereafter RHL) isset to 1:2, 1:3 and 1:4 for 10242 cells and 40962 cells, and the width of the grid transitionzone (for simplicity, WTZ) is set to 18◦ and 9◦to investigate their impacts on the modelsimulation. The ideal test cases, i.e. the cosine bell and global steady-state nonlinearzonal geostrophic flow, are carried out with the above settings. Simulation resultsshow that the larger the RHL is, the larger the resulting error is. It is obvious that the 1:4ratio gives rise to much larger errors than the 1:2 or 1:3 ratio; the errors resulting fromthe WTZ is much smaller than that from the RHL. No significant wave distortion orreflected waves are found when the fluctuation passes through the refinement region,and the error is significantly small in the refinement region. Therefore, when designinga local refinement scheme in the global model with SCVT, the RHL should be less than1:4, i.e., the error is acceptable when the RHL is 1:2 or 1:3.